Single-crystal positive electrode active material and preparation method and application thereof

By developing single-crystal positive electrode active materials with specific chemical composition and optimized preparation methods, the shortcomings in rate performance, cycle performance and energy density of solid-state lithium-ion batteries have been solved, and the overall improvement of battery performance has been achieved.

CN119852390APending Publication Date: 2025-04-18NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411945559.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing solid-state lithium-ion batteries have shortcomings in rate performance, cycle performance and energy density, and it is difficult to improve these performance indicators at the same time.

Method used

A single crystal positive electrode active material is developed, whose chemical composition and preparation method are optimized, including specific element composition and sintering process to improve the D50, BET, Ra and other characteristics of the material to form a material with high particle strength and uniform particle size distribution.

Benefits of technology

By using this single crystal positive electrode active material, the rate performance, cycle performance and energy density of the battery have been significantly improved, solving the problem of insufficient performance of traditional solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852390A_ABST
    Figure CN119852390A_ABST
Patent Text Reader

Abstract

The invention provides a single-crystal positive electrode active material and a preparation method and application thereof, the single-crystal positive electrode active material has the following chemical composition: LiaNixCoyMzA alpha D beta E gamma G delta O2, M is Mn and / or Al, A comprises at least one of Na, K, Cs, Ca, Sr, Ba, La and Ce, D comprises at least one of Al, Zr, Nb, Ta, Ti and Y, E comprises at least one of F, Cl, Br and I, and G comprises at least one of B, P and S; the D50 of the single-crystal positive electrode active material is 3-8 microns, the specific surface area BET is less than or equal to 0.5 m < 2 > / g, and the surface roughness Ra is less than or equal to 1 micron. When the single-crystal positive electrode active material provided by the invention is applied to a battery, the rate capability, the cycle performance and the energy density of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a single crystal positive electrode active material and a preparation method and application thereof. Background Art

[0002] Traditional lithium-ion batteries that use organic liquids as electrolytes have safety risks such as flammability, explosion, and solvent leakage. Compared with traditional lithium-ion batteries with liquid electrolytes, solid-state lithium batteries have advantages such as high specific energy and high safety, and are a better choice for solving power battery safety issues. However, in solid-state batteries, poor solid-solid contact will lead to higher interface impedance, affecting the conduction of ions and electrons, resulting in the rate performance and cycle performance of solid-state batteries being affected.

[0003] In the prior art, the problem of poor rate performance and cycle performance of solid-state batteries is solved by adding solid electrolytes to the positive electrode active materials, but the small proportion of positive electrode active materials will lead to low energy density of solid-state batteries. Therefore, developing a positive electrode active material that can simultaneously improve the rate performance, cycle performance and energy density of the battery is a technical problem that needs to be solved urgently at this stage. Summary of the invention

[0004] The main purpose of the present invention is to provide a single crystal positive electrode active material, which can be applied to a battery to improve the rate performance, cycle performance and energy density of the battery.

[0005] The present invention also provides a method for preparing a single crystal positive electrode active material, which can prepare the above single crystal positive electrode active material, and has a simple process and low cost.

[0006] The present invention also provides a composite positive electrode active material. Since the composite positive electrode active material includes the above-mentioned single crystal positive electrode active material, the composite positive electrode active material is applied to a battery to improve the rate performance, cycle performance and energy density of the battery.

[0007] The present invention also provides a positive electrode sheet. Since the positive electrode sheet includes the above-mentioned single crystal positive electrode active material or composite positive electrode active material, the positive electrode sheet is used in a battery to improve the rate performance, cycle performance and energy density of the battery.

[0008] The present invention also provides a battery. Since the battery includes the positive electrode sheet, the battery has higher rate performance, cycle performance and energy density.

[0009] In a first aspect, the present invention provides a single crystal positive electrode active material having a chemical composition as shown in Formula 1,

[0010] Li a Ni x Co y Mz A α D β E γ G δ O2, Formula 1,

[0011] Wherein, M is Mn and / or Al, A includes at least one of Na, K, Cs, Ca, Sr, Ba, La, and Ce, D includes at least one of Al, Zr, Nb, Ta, Ti, and Y, E includes at least one of F, Cl, Br, and I, G includes at least one of B, P, and S, 0.95≤a≤1.05, 0.80≤x<0.98, 0.02≤y≤0.20, 0.0005≤α≤0.01, 0.0005≤β≤0.01, 0≤γ≤0.01, 0.0005≤δ≤0.01, x+y<0.98, and z=1-xy;

[0012] The D50 of the single crystal positive electrode active material is 3-8 μm, and the specific surface area BET is ≤0.5 m 2 / g, surface roughness Ra≤1μm.

[0013] As described above, the single crystal positive electrode active material, A includes at least one of Sr, Ba, and Ce; D includes at least one of Al and Zr; E includes at least F; and G includes at least two of B, P, and S.

[0014] The single crystal positive electrode active material as described above has a lithium-nickel mixing rate of less than 3%.

[0015] The single crystal positive electrode active material as described above is subjected to X-ray diffraction analysis, and the half-peak width of the diffraction peak corresponding to the (104) crystal plane in the X-ray diffraction diagram of the single crystal positive electrode active material is less than 0.15°.

[0016] The single crystal positive electrode active material as described above, wherein the particle size distribution SPAN of the single crystal positive electrode active material is ≤2.

[0017] The single crystal positive electrode active material as described above, wherein the particle strength Rσ of the single crystal positive electrode active material is 300-800 MPa;

[0018] And / or, the circularity Re of the single crystal positive electrode active material is ≥ 0.5.

[0019] In a second aspect, the present invention provides a method for preparing the single crystal positive electrode active material as described above, comprising the following steps:

[0020] 1) sintering a first system including a single crystal positive electrode active material precursor, a first lithium source, an A source, and a D source in an oxygen-containing atmosphere for 8-20 hours at 800-1000° C. to obtain a first mixture; wherein the molar ratio N of the lithium element in the first lithium source to the sum of the nickel, cobalt, and M elements in the single crystal positive electrode active material precursor is 0<N<1.05;

[0021] 2) at 750-850° C., subjecting the second system including the first mixture and the second lithium source to secondary sintering in an oxygen-containing atmosphere for 8-20 hours to obtain a second mixture; wherein the molar ratio of the lithium element in the second lithium source to the sum of the nickel, cobalt and M elements in the single crystal positive active material precursor is 1.05-N;

[0022] 3) Sintering the third system including the second mixture and the G source three times at 150-350° C. for 8-20 hours to obtain the single crystal positive electrode active material.

[0023] In the preparation method as described above, the source of A is an oxide or a halide.

[0024] In a third aspect, the present invention provides a composite positive electrode active material, comprising the single crystal positive electrode active material as described above, the single crystal positive electrode active material prepared by the preparation method as described above, and a solid electrolyte.

[0025] The composite positive electrode active material as described above, wherein the ionic conductivity of the composite positive electrode active material is ≥10 -4 S / cm, electronic conductivity ≥10 -4 S / cm.

[0026] In the composite positive electrode active material as described above, the mass ratio of the single crystal positive electrode active material to the solid electrolyte is 85-90:10-15.

[0027] In a fourth aspect, the present invention provides a positive electrode sheet, comprising the single crystal positive electrode active material as described above, the single crystal positive electrode active material prepared by the preparation method as described above, or the composite positive electrode active material as described above.

[0028] In a fifth aspect, the present invention provides a battery comprising the positive electrode sheet as described above.

[0029] The present invention provides a single crystal positive electrode active material. By limiting the chemical composition, D50, BET, Ra and the relationship between D50, BET and Ra of the single crystal positive electrode active material, the single crystal positive electrode active material can be applied to a battery to improve the rate performance, cycle performance and energy density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present invention or related technologies. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0031] Figure 1 This is a SEM image of the single crystal positive electrode active material prepared in Example 1;

[0032] Figure 2 This is the SEM image of the single crystal positive electrode active material prepared in Comparative Example 3. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] In a first aspect, the present invention provides a single crystal positive electrode active material having a chemical composition as shown in Formula 1,

[0035] Li a Ni x Co y M z A α D β E γ G δ O2, Formula 1,

[0036] Wherein, M is Mn and / or Al, A includes at least one of Na, K, Cs, Ca, Sr, Ba, La, and Ce, D includes at least one of Al, Zr, Nb, Ta, Ti, and Y, E includes at least one of F, Cl, Br, and I, G includes at least one of B, P, and S, 0.95≤a≤1.05, 0.80≤x<0.98, 0.02≤y≤0.20, 0.0005≤α≤0.01, 0.0005≤β≤0.01, 0≤γ≤0.01, 0.0005≤δ≤0.01, x+y<0.98, and z=1-xy;

[0037] The D50 of the single crystal positive electrode active material is 3-8 μm, and the specific surface area BET is ≤0.5 m 2 / g, surface roughness Ra≤1μm.

[0038] The single crystal positive electrode active material of the present invention is applied to the battery to improve the rate performance and cycle performance of the battery, and the single crystal positive electrode active material is mixed with a solid electrolyte and used in a solid-state battery to significantly improve the energy density of the solid-state battery. It is speculated that this may be due to the D50 of the single crystal positive electrode active material being 3-8 μm and the specific surface area BET ≤ 0.5 m 2 / g, surface roughness Ra≤1μm, based on the fact that the solid-solid contact area between the large-sized single crystal positive electrode active material and the electrolyte is smaller than the contact area between the small-sized single crystal positive electrode active material and the electrolyte, a small amount of electrolyte material can be used to coat the positive electrode active material, realizing the transmission of the composite positive electrode lithium ion conductive network. The reduction in the use of inactive electrolyte materials can improve the mass energy density of the battery. In addition, large-sized positive electrode active materials are conducive to the improvement of the compaction density of the positive electrode active material, so that the thickness of the positive electrode sheet of the all-solid-state battery is reduced, which is conducive to improving the volume energy density of the all-solid-state battery. In addition, lower specific surface area and lower surface roughness will reduce the side reactions between the positive electrode active material and the electrolyte, reduce the interface impedance, and help improve the battery's rate performance, energy density and cycle performance.

[0039] In the chemical formula of the single crystal positive electrode active material of the present invention, element A can be used as a solvent to reduce the sintering temperature and inhibit lithium-nickel mixing; element D can be used as a lattice stabilizer, which is beneficial to the specific capacity of the single crystal positive electrode active material, thereby improving the energy density of the battery.

[0040] The present invention provides a single crystal positive electrode active material. By limiting the chemical composition, D50, BET, Ra and the relationship between D50, BET and Ra of the single crystal positive electrode active material, the single crystal positive electrode active material can be applied to a battery to improve the rate performance, cycle performance and energy density of the battery.

[0041] In some embodiments of the present invention, A includes at least one of Sr, Ba, and Ce; D includes at least one of Al and Zr; E includes at least F; and G includes at least two of B, P, and S.

[0042] As a preferred embodiment, in the chemical composition of the single crystal positive electrode active material of the present invention, when A includes at least one of Sr, Ba, and Ce, D includes at least one of Al and Zr, E includes at least F, and G includes at least two of B, P, and S, the specific capacity of the single crystal positive electrode active material can be further improved, the electronic and ionic conductivity of the battery can be improved, and the energy density, rate performance, and cycle performance of the battery can be improved.

[0043] In some embodiments of the present invention, the lithium-nickel mixing rate of the single crystal positive electrode active material is less than 3%.

[0044] In the present invention, when the lithium-nickel mixing rate of the single crystal positive electrode active material is less than 3%, the structure of the single crystal positive electrode active material is more stable, which is conducive to the rapid embedding and release of lithium ions during the charging and discharging process. The lower lithium-nickel mixing rate means that more lithium ions can be effectively stored and released in the material, thereby improving the energy density, rate performance and cycle performance of the battery.

[0045] In some embodiments of the present invention, after X-ray diffraction analysis, the half-peak width of the diffraction peak corresponding to the (104) crystal plane in the X-ray diffraction pattern of the single-crystalline positive electrode active material is less than 0.15°.

[0046] In the XRD spectrum of the single crystal positive electrode active material of the present invention, the half-peak width of the diffraction peak corresponding to the (104) crystal plane of the single crystal positive electrode active material in the X-ray diffraction pattern is less than 0.15°. Therefore, it is speculated that the primary particle size of the single crystal positive electrode active material of the present invention is relatively large, which is beneficial to the transmission of ions and electrons, and is beneficial to improving the electronic and ionic conductivity of the battery, thereby improving the rate performance, cycle performance and energy density of the battery.

[0047] In some embodiments of the present invention, the particle size distribution SPAN of the single crystal positive electrode active material is ≤2.

[0048] The particle size distribution SPAN of the single crystal positive electrode active material of the present invention is small, indicating that the particle size is relatively uniform, the gaps and irregularities between particles are reduced, the ion transmission path is optimized, the electron transmission resistance is reduced, and it is beneficial to increase the diffusion rate of ions, improve the charge and discharge efficiency and rate performance of the battery. At the same time, a compact stacking structure can be formed to improve the energy density of the battery.

[0049] The SPAN of the single crystal positive electrode active material is calculated according to the formula (D90-D10) / D50. The present invention does not limit the specific values ​​of D90, D50, and D10 of the above single crystal positive electrode active material, as long as the particle size distribution SPAN of the single crystal positive electrode active material is within the above range.

[0050] In some embodiments of the present invention, the particle strength Rσ of the single crystal positive electrode active material is 300-800 MPa;

[0051] And / or, the circularity Re of the single crystal positive electrode active material is ≥ 0.5.

[0052] The particle strength Rσ of the single crystal positive electrode active material in the present invention is within an appropriate range, and can withstand greater mechanical stress during the charge and discharge process, reducing the risk of particle breakage, thereby improving the cycle performance of the battery; in addition, it can also reduce the loss of active materials caused by particle breakage and improve the capacity retention rate of the battery. At the same time, the single crystal positive electrode active material with appropriate strength has good processability, reducing the risk of particle breakage during processing.

[0053] The single crystal positive electrode active material in the present invention has a high circularity and good contact with the electrolyte, which can optimize the ion transmission path, reduce the electron transmission resistance, and improve the rate performance, cycle performance and energy density of the battery.

[0054] In a second aspect, the present invention provides a method for preparing the single crystal positive electrode active material as described above, comprising the following steps:

[0055] 1) sintering a first system including a single crystal positive electrode active material precursor, a first lithium source, an A source, and a D source in an oxygen-containing atmosphere for 8-20 hours at 800-1000° C. to obtain a first mixture; wherein the molar ratio N of the lithium element in the first lithium source to the sum of the nickel, cobalt, and M elements in the single crystal positive electrode active material precursor is 0<N<1.05;

[0056] 2) at 750-850° C., subjecting the second system including the first mixture and the second lithium source to secondary sintering in an oxygen-containing atmosphere for 8-20 hours to obtain a second mixture; wherein the molar ratio of the lithium element in the second lithium source to the sum of the nickel, cobalt and M elements in the single crystal positive active material precursor is 1.05-N;

[0057] 3) Sintering the third system including the second mixture and the G source three times at 150-350° C. for 8-20 hours to obtain the single crystal positive electrode active material.

[0058] In the present invention, the single crystal positive electrode active material of the first aspect of the present invention can be prepared by subjecting the raw material to three sintering treatments.

[0059] Specifically, in step 1), the first lithium source can be at least one of lithium hydroxide, lithium carbonate, and lithium dihydrogen phosphate; the A source can be a compound containing the A element, which can serve as a cosolvent to reduce the sintering temperature and inhibit the mixing of lithium and nickel; the D source can be an oxide containing the D element, which can serve as a lattice stabilizer; and the present invention does not limit the specific form of the single crystal positive electrode active material precursor, as long as it can provide Ni, Co, and M elements. For example, (Ni x Co y M 1-x-y )(OH)2、(Ni x Co y M 1-x-y )CO3、(Ni x Co y M 1-x-y ) xAt least one of the precursors. When the single crystal positive electrode active material precursor, the first lithium source, the A source, and the D source are mixed to form the first system, the molar ratio N of the lithium element in the first lithium source to the sum of the nickel, cobalt, and M elements in the single crystal positive electrode active material precursor is 0<N<1.05, that is, high-temperature sintering is performed in a lithium-deficient state, and a single crystal positive electrode active material with a larger size can be obtained, and the dispersibility of the single crystal positive electrode active material is significantly improved.

[0060] In step 2), during the secondary sintering, the added second lithium source may be at least one of lithium hydroxide, lithium carbonate, and lithium dihydrogen phosphate, and the molar ratio of the lithium element in the second lithium source to the sum of the nickel, cobalt, and M elements in the single crystal positive active material precursor is 1.05-N. The purpose of adding the second lithium source is to supplement lithium, improve the kinetics of the surface of the single crystal positive active material or repair the surface oxygen defects, maintain the abundance of active lithium ions inside the battery, and perform capacity enhancement treatment, thereby improving the energy density of the battery.

[0061] In step 3), the three sinterings can be carried out in oxygen, air or inert atmosphere. The purpose of adding the G source for the three sinterings is to coat the G source on the surface of the single crystal positive electrode active material, improve the interface stability between the single crystal positive electrode active material and the electrolyte, and improve the cycle performance of the battery.

[0062] The preparation method of the present invention can prepare the single crystal positive electrode active material of the first aspect. The single crystal positive electrode active material is applied to a battery to improve the rate performance, cycle performance and energy density of the battery.

[0063] In some embodiments of the present invention, the source of A is an oxide or a halide.

[0064] When source A in the present invention is an oxide or a halide, the dissolution effect as a co-solvent is better, which can further reduce the sintering temperature, reduce the lithium-nickel mixing of the single crystal positive electrode active material, improve the stability of the battery, improve the ion and electronic conductivity, and avoid the decrease in battery energy density.

[0065] The surface roughness Ra of the single crystal positive electrode active material in the present invention is affected by the temperature and time of the primary sintering and the type of the A source.

[0066] The particle strength Rσ, specific surface area BET, circularity Re, D50 and particle size distribution SPAN of single crystal positive electrode active materials are affected by the primary sintering temperature and time.

[0067] The lithium-nickel mixing is affected by the temperature and time of the primary sintering, the molar ratio N of the lithium element in the first lithium source to the sum of the nickel, cobalt and M elements in the single crystal positive electrode active material precursor, and the type of the A source.

[0068] In a third aspect, the present invention provides a composite positive electrode active material, comprising the single crystal positive electrode active material as described above, the single crystal positive electrode active material prepared by the preparation method as described above, and a solid electrolyte.

[0069] The composite positive electrode active material of the present invention comprises the above-mentioned single crystal positive electrode active material and a solid electrolyte, so the composite positive electrode active material is applied to a battery to improve the rate performance, cycle performance and energy density of the battery. Among them, the solid electrolyte can be at least one of an oxide solid electrolyte, a halide solid electrolyte, and a sulfide solid electrolyte. The oxide solid electrolyte can be at least one of LATP, LLZO, and LLTO materials. The halide solid electrolyte can be Li3InCl6, Li2ZrCl6, Li2YZrCl6, LiNbOCl4, LiTaOCl4, Li3ZrCl4O 1.5 At least one of the materials, the sulfide solid electrolyte can be Li2S-P2S5, Li3PS4, Li7P3S 11 、Li6PS5Cl、Li 5.5 PS 4.5 Cl 1.5 , Li 7-x PS 6-x Cl x (0<x<1.7), Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , Li 10 GeP2S 12 At least one of the materials.

[0070] The preparation method of the composite positive electrode active material of the present invention may include the following steps: physically mixing the single crystal positive electrode active material and the solid electrolyte in a certain proportion, so that the solid electrolyte is evenly coated on the surface of the single crystal positive electrode active material to obtain a mixed system, and then heat-treating the mixed system at 0-300°C, preferably 50-150°C, under the protection of an inert gas for 1-5h to obtain a composite positive electrode active material. The physical mixing may be ball milling, degassing or banburying, and the mixing time may be 0.5-3h.

[0071] In some embodiments of the present invention, the ionic conductivity of the composite positive electrode active material is ≥10 -4 S / cm, electronic conductivity ≥10 -4 S / cm.

[0072] The ionic conductivity of the composite positive electrode active material in the present invention is ≥10 -4 S / cm, electronic conductivity ≥10 -4S / cm, in a higher range, is beneficial to the improvement of rate performance, cycle performance and energy density in the battery.

[0073] In some embodiments of the present invention, the mass ratio of the single crystal positive electrode active material to the solid electrolyte is 85-90:10-15.

[0074] In the composite positive electrode active material of the present invention, the mass ratio of the single crystal positive electrode active material to the solid electrolyte is 85-90:10-15, preferably 85:15. The proportion of the single crystal positive electrode active material is relatively high, which is beneficial to the specific capacity. Therefore, the composite positive electrode active material is applied to the battery to improve the rate performance, cycle performance and energy density of the battery.

[0075] In a fourth aspect, the present invention provides a positive electrode sheet, comprising the single crystal positive electrode active material as described above, the single crystal positive electrode active material prepared by the preparation method as described above, or the composite positive electrode active material as described above.

[0076] The positive electrode sheet provided by the present invention includes a conductive agent and a binder in addition to a single crystal positive electrode active material and an electrolyte material. The present invention does not particularly limit the specific types of the conductive agent and the binder. The conductive agent, the binder and other components can be selected from conventional materials in the art. For example, the conductive agent can be selected from at least one of conductive carbon black, carbon nanotubes, vapor-grown carbon fiber (VGCF), conductive graphite, and graphene, and the binder can be selected from at least one of polyvinylidene fluoride (PVDF), tetrafluoroethylene (PTFE), polyacrylate polymers, polyimide, styrene-butadiene rubber, nitrile rubber, and propylene-butadiene rubber.

[0077] Since the positive electrode sheet provided by the present invention includes the above-mentioned single crystal positive electrode active material or composite positive electrode active material, the positive electrode sheet is used in a battery to improve the rate performance, cycle performance and energy density of the battery.

[0078] In a fifth aspect, the present invention provides a battery comprising the positive electrode sheet as described above.

[0079] The battery in the present invention can be a solid-state battery or a liquid battery. When it is a solid-state battery, in addition to the positive electrode sheet, it also includes a solid electrolyte and a negative electrode sheet. Among them, the solid electrolyte can use conventional electrolytes in the art, for example, at least one of the oxide solid electrolytes LATP, LLZO, and LLTO materials, and the halide solid electrolytes Li3InCl6, Li2ZrCl6, Li2YZrCl6, LiNbOCl4, LiTaOCl4, Li3ZrCl4O 1.5 At least one of the materials, sulfide solid electrolyte Li2S-P2S5, Li3PS4, Li7P3S 11 、Li6PS5Cl、Li 5.5 PS4.5 Cl 1.5 , Li 7-x PS 6-x Cl x (0<x<1.7), Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , Li 10 GeP2S 12 At least one of the materials. The negative electrode active material in the negative electrode sheet can be at least one of the currently commonly used negative electrode active materials, such as graphite, hard carbon, soft carbon, mesophase carbon microspheres, silicon-based negative electrode materials (mainly including silicon oxide, silicon-carbon negative electrode), tin-based negative electrode materials (mainly including tin, tin alloy), etc.

[0080] When it is a liquid battery, in addition to the positive electrode sheet, it also includes a separator, a negative electrode sheet and an electrolyte. Among them, the composition of the negative electrode sheet can refer to the conventional negative electrode sheet in the art, and the separator can also be a separator conventionally used in the art, such as PP film, PE film, etc.

[0081] Since the battery provided by the present invention includes the above-mentioned positive electrode sheet, the battery has excellent rate performance, cycle performance and energy density.

[0082] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0083] Example 1

[0084] The preparation method of the composite positive electrode active material of this embodiment comprises the following steps:

[0085] 1) 1 mol of single crystal positive electrode active material precursor (Ni 0.83 Co 0.12 Mn 0.05 )(OH)2, 1.0molLiOH·H2O, 0.005mol SrO, and 0.009mol ZrO2 are mixed to obtain a first system, wherein the molar ratio of the lithium element in the first lithium source to the total of the nickel, cobalt, and Mn elements in the single crystal positive electrode active material precursor is 1. The first system is placed in an oxygen atmosphere for a primary sintering at a temperature of 920°C for 12 hours to obtain a first mixture;

[0086] 2) 1 mol of the first mixture and 0.05 mol of the second lithium source LiOH·H2O are mixed to obtain a second system, wherein the molar ratio of the lithium element in the second lithium source to the sum of the nickel, cobalt, and Mn elements in the single crystal positive electrode active material precursor is 0.05. The second system is placed in an oxygen atmosphere for secondary sintering at a temperature of 800°C for 12 hours to obtain a second mixture;

[0087] 3) 1 mol of the second mixture was mixed with 0.005 mol of H3BO3 to obtain a third system, and the third system was placed in an inert atmosphere and sintered three times at a temperature of 300°C for 12 hours to obtain a single crystal positive electrode active material Li 1.02 Ni 0.83 Co 0.12 Mn 0.05 Sr 0.005 Zr 0.009 B 0.005 O2.

[0088] 4) The above-mentioned single crystal positive electrode active material and the solid electrolyte LPSC are ball-milled to obtain a mixed system, wherein the mass ratio of the polycrystalline positive electrode active material to the solid electrolyte LPSC is 85:15, and the mixing time is 1 hour; the mixed system is heat-treated at 55° C. for 3 hours in a N2 atmosphere to obtain a composite positive electrode active material.

[0089] Example 2

[0090] The preparation method of the composite positive electrode active material of Example 2 is basically the same as that of Example 1, except that 0.005 mol BaCO3, 0.001 mol Al2O3, and 0.001 mol AlF3 are added in step 1) to obtain a single crystal positive electrode active material Li 1.02 Ni 0.83 Co 0.12 Mn 0.05 Ba 0.005 Al 0.003 F 0.003 O2.

[0091] Example 3

[0092] The preparation method of the composite positive electrode active material in Example 3 is basically the same as that in Example 1, except that 0.001 mol CeF3 and 0.001 mol LaF3 are added in step 1) to obtain a single crystal positive electrode active material Li 1.02 Ni 0.83 Co 0.12 Mn 0.05 Ce 0.001 La 0.001 F 0.006 B 0.005 O2.

[0093] Example 4

[0094] The preparation method of the composite positive electrode active material of Example 4 is basically the same as that of Example 1, except that the primary sintering temperature is changed to 900°C and the secondary sintering temperature is changed to 820°C.

[0095] Example 5

[0096] The preparation method of the composite positive electrode active material of Example 5 is basically the same as that of Example 1, except that the secondary sintering temperature is changed to 840°C and the tertiary sintering temperature is changed to 330°C.

[0097] Example 6

[0098] The preparation method of the composite positive electrode active material of Example 6 is basically the same as that of Example 1, except that the secondary sintering temperature is changed to 830°C and the tertiary sintering temperature is changed to 310°C.

[0099] Example 7

[0100] The preparation method of the composite positive electrode active material in Example 7 is basically the same as that in Example 1, except that the mass ratio of the single crystal positive electrode active material to the solid electrolyte is changed to 90:10.

[0101] Comparative Example 1

[0102] The preparation method of the composite positive electrode active material of Comparative Example 1 comprises the following steps:

[0103] 1) Weigh nickel sulfate, cobalt sulfate and manganese sulfate according to the stoichiometric ratio of nickel element: cobalt element: manganese element = 0.93: 0.06: 0.01, and use the above materials to prepare a soluble salt solution with a total metal ion concentration of nickel, cobalt and manganese of 110 g / L;

[0104] 2) Pump 30L of 4g / L ammonia solution into the high-temperature and high-pressure reactor as the reactor bottom liquid, introduce 99.5% pure oxygen into the reactor, turn on the stirring device of the reactor, and control the temperature of the reactor to 50°C;

[0105] 3) The soluble salt solution prepared in step 1) is fully mixed with LiOH, and the ratio of the two is determined according to the molar ratio Li:M (M represents all metal elements in the soluble salt solution) = 0.4; at the same time, a NaOH solution with a concentration of 320g / L and an ammonia solution with a concentration of 120g / L are added to the reactor, the reaction temperature is controlled at 150°C, and the oxygen partial pressure is controlled at 2.5MPa, so that the reaction system undergoes a coprecipitation reaction under the above reaction conditions, and the reaction time is 5 hours; after the coprecipitation reaction is completed, the obtained precipitate is washed and dried to obtain a pre-lithiation primary positive electrode active material with a relatively high degree of dispersion;

[0106] 4) The pre-lithiation primary positive electrode active material prepared in step 3) is fully mixed with LiOH-LiNO3 molten salt, and the ratio of the two is determined according to the molar ratio Li:M=0.64; the mixture thus obtained is placed in a heating reaction chamber of a high-temperature furnace, oxygen is introduced into the reaction chamber, and the mixture is heated to 1300°C in an oxygen atmosphere and kept warm for 10 hours. The primary positive electrode active material continues to dissolve and recrystallize in the high temperature environment, and then the product is cooled to room temperature with the furnace. After the material is discharged, it is ground, rolled, separated, and sieved to obtain the corresponding layered NCM single crystal positive electrode active material.

[0107] 5) The above-mentioned single crystal positive electrode active material and the solid electrolyte LPSC are ball-milled to obtain a mixed system, wherein the mass ratio of the polycrystalline positive electrode active material to the solid electrolyte LPSC is 85:15, and the mixing time is 1 hour; the mixed system is heat-treated at 55° C. for 3 hours in a N2 atmosphere to obtain a composite positive electrode active material.

[0108] Comparative Example 2

[0109] The preparation methods of the composite positive electrode active material of Comparative Example 2 and Comparative Example 1 are basically the same, except that the heating temperature in step 4) is changed to 600°C.

[0110] Comparative Example 3

[0111] The preparation method of the composite positive electrode active material of Comparative Example 3 comprises the following steps:

[0112] 1) 1 mol of single crystal positive electrode active material precursor (Ni 83 Co 12 Mn5) (OH) 2, 1.02 mol LiOH·H2O, and 0.009 mol ZrO2 are mixed to obtain a first system, wherein the molar ratio of the lithium element in the first lithium source to the total of the nickel, cobalt, and Mn elements in the single crystal positive electrode active material precursor is 1.02. The first system is placed in an oxygen atmosphere for a first sintering at a temperature of 850°C for 12 hours to obtain a first mixture;

[0113] 2) 1 mol of the first mixture and 0.03 mol of the second lithium source LiOH·H2O are mixed to obtain a second system, wherein the molar ratio of the lithium element in the second lithium source to the sum of the nickel, cobalt, and Mn elements in the single crystal positive electrode active material precursor is 0.03. The second system is placed in an oxygen atmosphere for secondary sintering at a temperature of 500°C for 12 hours to obtain a second mixture;

[0114] 3) 1 mol of the second mixture was mixed with 0.005 mol of H3BO3 to obtain a third system, and the third system was placed in an inert atmosphere and sintered three times at a temperature of 300°C for 12 hours to obtain a single crystal positive electrode active material Li 1.02 Ni0 0.83 Co 0.12 Mn 0.05 Zr 0.009 B 0.005 O2.

[0115] 4) The above-mentioned single crystal positive electrode active material and the solid electrolyte LPSC are ball-milled to obtain a mixed system, wherein the mass ratio of the polycrystalline positive electrode active material to the solid electrolyte LPSC is 85:15, and the mixing time is 1 hour; the mixed system is heat-treated at 55° C. for 3 hours in a N2 atmosphere to obtain a composite positive electrode active material.

[0116] Test example:

[0117] 1. D50: The particle size of the single crystal positive electrode active material powder sample was tested using a laser particle size analyzer (MasterSizer 2000).

[0118] 2. BET: Weigh the total weight of the empty test tube and the stopper, soak the single crystal positive electrode active material powder sample to be tested in anhydrous ethanol for 4 hours, then take out the powder sample and put it in an oven at 105°C for half an hour, then put the powder sample into the sample tube, and weigh the total weight of the powder sample, the test tube and the stopper to calculate the sample mass; turn on the degassing station, put the test tube containing the powder sample into the degassing station at a temperature of 105°C, purge with nitrogen (pure nitrogen) for 30 minutes, cool for 15 minutes, and test at a temperature of 25°C and a humidity of 60%; take P / P0 with points in the range of 0.05~0.25 as the x-axis and P / V(P0-P) as the Y-axis, and make a linear fit based on the BET equation to obtain the slope and intercept of the straight line to calculate the BET specific surface area of ​​the powder sample.

[0119] 3. Ra: Place the single crystal positive electrode active material on the vacuum adsorption stage of the atomic force microscope. The scanning adopts the tapping measurement mode. The AFM scanning range is 18μm×18μm, the scanning points are 256×256, and the single line measurement time is 1.56s. After the scanning is completed, the positive electrode material is selected and the roughness value Ra is directly read.

[0120] 4. SPAN: Use a laser particle size analyzer to test the particle size of the single crystal positive electrode active material, read the D10, D50, and D90 values, SPAN = (D90-D10) / D50.

[0121] 5. Rσ: The particle strength of the single crystal positive electrode active material was tested using Shimadzu DUH-211S ultra-micro dynamic hardness tester.

[0122] 6. Re: Use Metis software to scan the single crystal positive electrode active material particles in SEM to obtain the projected area S and perimeter L. The circularity Re calculation formula is: Re=4πS / L 2 .

[0123] 7. Lithium-nickel mixing ratio: The diffraction peak data of the single crystal positive electrode active material is obtained through XRD testing. After overall refinement with the software Topas, the lithium-nickel mixing result of the single crystal positive electrode active material is calculated.

[0124] 8. Specific capacity: The above-mentioned single crystal positive electrode active materials, sulfide solid electrolyte (Li6PS5Cl), and conductive agent (VGCF) were weighed into a mortar at a mass ratio of 85:15:1 and manually mixed for more than 30 minutes to obtain a mixed material, and then 1% by mass (accounting for 1% of the above-mentioned mixed material) of polytetrafluoroethylene particles (PTFE) was added, and the mixture was heated at 150°C on a heating table for 5 minutes and then manually ground into a film to pre-fiberize the PTFE. The obtained film was then heated and rolled on a calender at a rolling temperature of 100°C. The thickness of the obtained film was adjusted by controlling the gap width between the two hot pressing rollers. The composite positive electrode material film was repeatedly rolled to obtain a shaped composite positive electrode material film with a thickness of 40-60µm. The composite positive electrode material film was calendered to the surface of a 15µm thick Al foil current collector to obtain a positive electrode sheet. The above positive electrode sheet is die-cut into a disc with a diameter of 8mm, and then stacked and cold-pressed with Li6PS5Cl sulfide solid electrolyte membrane and LiIn negative electrode in a glove box filled with Ar atmosphere to obtain an all-solid-state battery. At 25°C, it is charged to 4.5V at a constant current rate of 0.1C / 1C, and then charged at a constant voltage at 4.5V to a current equal to 0.05C. The charging capacity at this time is recorded as the first cycle charging capacity. After standing for 5 minutes, it is discharged at a constant current rate of 0.1C / 1C to a voltage of 2.5V. The discharge capacity this time is recorded as the first cycle discharge capacity of the battery.

[0125] 9. Energy density: Use a battery charge and discharge tester to charge the battery to 4.5V at 0.2C constant current at 25℃, then charge it at constant voltage until the current drops to 0.05C. After standing for 5 minutes, discharge the battery to 2.5V at 0.2C constant current, and record the battery's first discharge capacity Q. 放 and the first discharge energy E 放 , weigh the battery mass as W, and calculate the mass energy density ED=E 放 / W.

[0126] 10. Rate performance: At 25°C, the all-solid-state battery is charged at a constant current rate of 0.1C to a voltage of 4.5V, then charged at a constant voltage at a voltage of 4.5V to a current equal to 0.05C, then allowed to stand for 5 minutes, and then discharged at a constant current rate of 0.1C to a voltage of 2.5V. The capacity at this time is recorded as the discharge capacity at a rate of 0.1C; after standing for 10 minutes, the battery is charged at a constant current rate of 1C to a voltage of 4.5V, then charged at a constant voltage at a voltage of 4.5V to a current equal to 0.05C, then allowed to stand for 5 minutes, and then discharged at a constant current rate of 1C to a voltage of 2.5V. The capacity at this time is recorded as the discharge capacity at a rate of 1C. The ratio of the discharge capacity at a rate of 1C to the discharge capacity at a rate of 0.1C is the 1C rate performance.

[0127] 11. Cycle performance: The all-solid-state battery is charged at a constant current of 0.1C to a voltage of 4.5V at 25°C, then charged at a constant voltage of 4.5V to a current equal to 0.05C, then allowed to stand for 5 minutes, and then discharged at a constant current of 0.1C to a voltage of 2.5V. This cycle test is repeated until the capacity decays to 80%, and the number of cycles is recorded.

[0128] Figure 1 This is the SEM image of the single crystal positive electrode active material prepared in Example 1.

[0129] from Figure 1 It can be seen that the single crystal positive electrode active material prepared in Example 1 is relatively large in size.

[0130] Figure 2 This is the SEM image of the single crystal positive electrode active material prepared in Comparative Example 3.

[0131] from Figure 2 It can be seen that the single crystal positive electrode active material prepared in Comparative Example 3 is smaller in size.

[0132] Table 1

[0133]

[0134] Table 2

[0135]

[0136] It can be seen from Table 1 that, compared with the comparative example, the single crystal positive electrode active material provided by the present invention, by limiting the chemical composition, D50, BET, Ra and the relationship between D50, BET and Ra of the single crystal positive electrode active material, can be applied to the battery, which can improve the rate performance, cycle performance and energy density of the battery.

[0137] From the comparison between Examples 1-7 and Comparative Examples 1-3, it can be seen that the single crystal positive electrode active material provided by the present invention is applied to a battery to improve the specific capacity, rate performance, cycle performance and energy density of the battery.

[0138] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A single crystal positive electrode active material, characterized in that: Having the chemical composition shown in Formula 1, Li a Ni x Co y M z A α D β E γ G δ O2, formula 1 Wherein, M is Mn and / or Al, A includes at least one of Na, K, Cs, Ca, Sr, Ba, La, and Ce, D includes at least one of Al, Zr, Nb, Ta, Ti, and Y, E includes at least one of F, Cl, Br, and I, G includes at least one of B, P, and S, 0.95≤a≤1.05, 0.80≤x<0.98, 0.02≤y≤0.20, 0.0005≤α≤0.01, 0.0005≤β≤0.01, 0≤γ≤0.01, 0.0005≤δ≤0.01, x+y<0.98, and z=1-xy; The D50 of the single crystal positive electrode active material is 3-8 μm, and the specific surface area BET is ≤0.5 m 2 / g, surface roughness Ra≤1μm.

2. The single crystal positive electrode active material according to claim 1, characterized in that: The A includes at least one of Sr, Ba, and Ce; the D includes at least one of Al and Zr; the E includes at least F; and the G includes at least two of B, P, and S.

3. The single crystal positive electrode active material according to claim 1 or 2, characterized in that: The lithium-nickel mixing rate of the single crystal positive electrode active material is less than 3%.

4. The single crystal positive electrode active material according to any one of claims 1 to 3, characterized in that: X-ray diffraction analysis shows that the half-peak width of the diffraction peak corresponding to the (104) crystal plane in the X-ray diffraction diagram of the single-crystal positive electrode active material is less than 0.15°.

5. The single crystal positive electrode active material according to any one of claims 1 to 4, characterized in that: The particle size distribution SPAN of the single crystal positive electrode active material is ≤2.

6. The single crystal positive electrode active material according to any one of claims 1 to 5, characterized in that: The particle strength Rσ of the single crystal positive electrode active material is 300-800 MPa; And / or, the circularity Re of the single crystal positive electrode active material is ≥ 0.

5.

7. A method for preparing a single crystal positive electrode active material according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) sintering a first system including a single crystal positive electrode active material precursor, a first lithium source, an A source, and a D source in an oxygen-containing atmosphere for 8-20 hours at 800-1000° C. to obtain a first mixture; wherein the molar ratio N of the lithium element in the first lithium source to the sum of the nickel, cobalt, and M elements in the single crystal positive electrode active material precursor is 0<N<1.05; 2) at 750-850° C., subjecting the second system including the first mixture and the second lithium source to secondary sintering in an oxygen-containing atmosphere for 8-20 hours to obtain a second mixture; wherein the molar ratio of the lithium element in the second lithium source to the sum of the nickel, cobalt and M elements in the single crystal positive active material precursor is 1.05-N; 3) Sintering the third system including the second mixture and the G source three times at 150-350° C. for 8-20 hours to obtain the single crystal positive electrode active material.

8. The preparation method according to claim 7, characterized in that: The A source is an oxide or a halide.

9. A composite positive electrode active material, characterized in that: It comprises the single crystal positive electrode active material according to any one of claims 1 to 6, the single crystal positive electrode active material prepared by the preparation method according to claim 7 or 8, and a solid electrolyte.

10. The composite positive electrode active material according to claim 9, characterized in that: The ionic conductivity of the composite positive electrode active material is ≥10 -4 S / cm, electronic conductivity ≥10 -4 S / cm.

11. The composite positive electrode active material according to claim 9 or 10, characterized in that: The mass ratio of the single crystal positive electrode active material to the solid electrolyte is 85-90:10-15.

12. A positive electrode sheet, characterized in that: It comprises the single crystal positive electrode active material according to any one of claims 1 to 6, the single crystal positive electrode active material prepared by the preparation method according to claim 7 or 8, and the composite positive electrode active material according to any one of claims 9 to 11.

13. A battery, characterized in that: Including the positive electrode sheet as claimed in claim 12.